The mental health professional and the new technologies : a handbook for practice today - Maheu, Marlene M. (Lawrence Erlbaum Associates, 2005)
"In this wide-ranging and practical handbook, five experts, each with a different vantage point and training, systematically guide readers through the new practice arenas already made possible by current information technologies - ranging from internet-wired officers to wearable computers - and point to those on the horizon. Throughout, the authors clearly define terminology for the beginner and illuminate their points with clinical vignettes and first-person accounts of the experience of pioneering practitioners."--Jacket